Use of Artificial Intelligence Technology AI News Presenter in the News Production Process at TVOne.ai - Ayu Karunianingsih, Diyah; Sarifah, Siti; Korina Relawati, Dwi; Dwi Setyorini, Mutiara; Utomo, Ardian (COMMICAST, 2025)
The rapid pace of digital technology today is marked by the massive development of artificial intelligence technology, including the utilization of artificial technology in the news production process. This research examines the application of artificial intelligence (AI) in the news production process carried out by TVOne.ai. The research method used in this study was descriptive qualitative, conducted using a grounded theory approach with a focus on analyzing the application of artificial intelligence technology in the news production process, specifically the utilization of AI news presenters.  This study uses a grounded theory approach to examine the integration of AI news presenters in TVOne.ai news production. The findings indicate that news production entirely uses AI technology, from data collection to presentation, offering efficiency but posing challenges related to ethics and public acceptance. In addition, the research findings reveal that the news production process at TVOne.ai differs from conventional journalism practices. News is produced entirely using AI technology and applications, from data collection, voice cloning, to the presentation of AI presenters.  The study concludes that the use of Artificial Intelligence technology, specifically the AI news presenter at TVOne.ai, enhances the efficiency and consistency of the news production process. AI presenters enable faster content delivery, reduce operational costs, and ensure 24-hour broadcasting capabilities. However, human oversight remains essential to maintain journalistic accuracy, ethical standards, and audience trust the results of this research are expected to contribute knowledge about the news production process with the utilization of AI, both for academics, researchers, and media practitioners.